Extraskeletal myxoid chondrosarcoma of the penis: Description of a rare tumor arising in an unusual location - Khaled A. Murshed (14151927) (2022)
Extraskeletal myxoid chondrosarcoma (EMC) is a rare malignant soft tissue tumor that most commonly arises in the extremities. Its occurrence in the genitourinary tract is extremely uncommon. We present an 82-year-old man who was found to have incidental pulmonary metastasis by imaging studies. The biopsy findings from the lung were in favor of metastatic EMC. The primary mass was found to be located at the penile root, which was confirmed to be EMC. This case adds to the few reported cases of EMC arising in the perineal region, and sheds light on the clinical behavior of this soft tissue tumor. Other Information Published in: Urology Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.eucr.2022.102151